"Because we're all different" – Everyday experiences of belonging among young people from immigrant backgrounds in Tottenham. Issue 116 (November 2020) - Visser, Kirsten
Highlights: Belonging is dynamic and situational, and should be seen as a process of seeking and being granted belonging. Feeling rejected by people outside Tottenham negatively impacted on youths' sense of belonging to British society. Local identity provided the youths with an alternative by means of which they can feel at home. We should worry about youths' local attachment being a consequence of social exclusion from the rest of the society. Abstract: The United Kingdom, as most other West European countries, is being confronted with increasing diversity in terms of ethnicity, language, religion and identity. Questions on the desirability and possibility of a multicultural society are a topic of debate. In the last decade, the public debate has increasingly centred on young people from immigrant backgrounds, often referring to their perceived failure to assimilate to the host society. Issues of 'belonging', either to the host society or the country of their parents are central in this debate. Little scholarly research, however, has paid attention to experience and negotiation of belonging of the young people from immigrant backgrounds themselves. In this study I look at how young people from immigrant backgrounds (12–19 years old) living in a highly diverse neighbourhood (Tottenham, London), experience and negotiate belonging to British society and to their neighbourhood. In this paper I show that (1) belonging negotiated by the young people in Tottenham is dynamic and situational, and should be seen as a process of seeking and being granted belonging which happens at different scales; and (2) whereas London is a city famous for its image of cosmopolitanism, openness, and tolerance we also see that the young people in the study do not always experience it as such. Expressing a strong sense of belonging to Tottenham could be seen as a reaction to not always feeling part of British society.